CONTRASTIVE ANALYSIS OF TONGUE TWISTERS FORMED ON THE BASIS OF WIND LEXICON IN UZBEK AND ENGLISH LANGUAGES - Kosimov Botir Saidvali ugli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This article provides a contrastive linguistic analysis of tongue twisters formed on the basis of the wind lexicon in Uzbek and English languages. It investigates their semantic features, phonetic structure, stylistic devices, and cultural associations. The study reveals that while both languages employ alliteration and sound symbolism to imitate the movement and force of wind, Uzbek tongue twisters display a stronger presence of expressive morphology and natural imagery, whereas English ones emphasize rhythmic fluency and airy consonant clusters. The findings highlight how wind-related vocabulary creates specific semantic and phonetic complexity across languages.